Constructing equality: developing an intersectionality analysis to achieve equality rights for the girl child subject to South African customary law - Amoah, Jewel Dee Afua (Department of Public Law, 2016)
Equality, an ideal that like should be treated alike, lies at the heart of most national constitutions and all international human rights instruments. Despite its ancient origins, however, this principle is far from being achieved in practice. Hence, in the search for full substantive equality, critical legal scholars put forward a theory and accompanying analytical framework of intersectionality. Using South Africa as an example, this thesis examines the realisation of the constitutional promise of equality for those who have been traditionally marginalised by reason of their intersecting race and gender identities. The process of navigating this identity intersection is complicated by the cultural diversity that is a feature of South African society. The Constitution nevertheless, encourages such diversity, and goes even further to give equal recognition to the coexisting systems of common and customary law that are rooted in Western and post-colonial African cultures, respectively. It follows that a full understanding of the different legal and social contexts in which a rights claimant lives is critical to the achievement of substantive equality.